Student Perceptions of Scholarly Writing - Shirley Peganoff O'Brien; Dory Marken; Kelsey Bennett Petrey (Scholarworks @ WMU, 2016)
Learning the process of scholarly writing, including the significance of peer review, is an essential element in the preparation of students for professional practice. This descriptive research study, using Scholarship of Teaching and Learning methodology, explores one approach to teaching scholarly writing in an occupational science/occupational therapy curriculum. The writing assignment was designed to offer multiple points for feedback and revision and instructional features to reinforce learning. A survey of students [n = 169] participating in this scholarly writing project was conducted yearly to gather their perceptions of learning. The results revealed four key elements: instructional strategies are needed to support scholarly writing, students value explicit instructor feedback, a successful writing experience opens the possibility for students to write in their professional future, and students will develop the habits of a writer given structure and pedagogical considerations in the assignment construction. This experience shows students will work to achieve the expected standard for scholarship once writing is made an essential part of the course and their efforts are supported by scaffolding the assignment. Through this experience, it was also learned students need opportunities for repetition and practice to refine scholarly writing. Suggestions for future research are proposed.